The Language of “Non-Medical” Illness in Konjo: Ethnolinguistic Insights for Health Communication - Sri Ningsih; Didit Kurniadi; Abdul Muhid; Rusdiana Junaid (Universitas Islam Negeri Palopo, 2026)
This article examines how Konjo speakers in the Ammatoa Kajang community name and interpret three local illness categories — kasamperoang, pappitaba, and poppo’ — and how attention to those categories can strengthen culturally responsive health communication and English for Specific Purposes (ESP) preparation for midwifery students. In this context, “non-medical” does not mean unreal or outside care; rather, it refers to illness episodes whose local explanation includes place, relational disturbance, emotion, adat, and unseen agency alongside bodily signs. Drawing on ethnographic fieldwork in Tana Toa village, Bulukumba, in May to July 2025, including interviews with sanro, pregnant and postpartum women, husbands, and village leaders, the research finds that kasamperoang links vulnerable children to movement through sensitive places; pappitaba indexes dizziness, burden, fear, shame, and social-emotional disturbance; and poppo’ marks a sudden, intrusive attack that requires rapid protection. Families move rationally between sanro and biomedical services based on severity and perceived cause. The main issue is one of category translation: reducing local terms to ‘fever’ or ‘stress’ loses critical causal and relational information. The article concludes with implications for culturally grounded history-taking and local-culture-based ESP materials in health education.